A Novel Beam Downtilt Selection Method for 3D Active Antenna System Based Cellular Network - Kai Wang; Liang Zhang; Guoping Tan (Dianxin kexue)
Traditional 2D active antenna system can only carry on horizontal beam steering in cellular mobile radio system. The existing 3D active antenna system based cellular network can obtain large throughput gain with the use of vertical beam steering. The existing beam downtilt selection method for 3D active antenna system is based on the information of pitch angle. The received power of the user is very low. A novel beam downtilt selection method for 3D active antenna system was proposed to improve the received power, which is based on the received reference signal power. Simulation results show that the proposed method can improve the average throughput of the cell and the system performance sharply.